2022
DOI: 10.1186/s12872-022-02544-6
|View full text |Cite
|
Sign up to set email alerts
|

Conventional fluoroscopy-guided versus zero-fluoroscopy catheter ablation of supraventricular tachycardias

Abstract: Purpose The aim of this study was to evaluate the safety and efficacy of zero-fluoroscopy (ZF) catheter ablation (CA) for supraventricular tachycardias (SVT). Methods 584 consecutive patients referred to our institution for CA of SVT were analysed. Patients were categorised into two groups; zero-fluoroscopy (ZF) group and conventional fluoroscopy (CF) group. The ZF group was further divided into two subgroups (adults and paediatric). Patient charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…16 We applied repetitive PFE delivery near the target in order to create an expanded range of lesions. 15 , 17 In this study, we suggest that the 3-PFA modality for bonus lesions is rational for the elimination of APs. Although the cumulative damage mainly determined the effects of PFA protocol, the effects of a given population of cardiomyocytes and its neighbouring environment should not be neglected.…”
Section: Discussionmentioning
confidence: 70%
“…16 We applied repetitive PFE delivery near the target in order to create an expanded range of lesions. 15 , 17 In this study, we suggest that the 3-PFA modality for bonus lesions is rational for the elimination of APs. Although the cumulative damage mainly determined the effects of PFA protocol, the effects of a given population of cardiomyocytes and its neighbouring environment should not be neglected.…”
Section: Discussionmentioning
confidence: 70%
“…In thermal ablation modalities, however, procedural outcomes of zero-fluoroscopy approach have been shown to be comparable to the conventional fluoroscopy-based approach. 12 Over the years extensive literature has accumulated that describes benefits of using ICE. In a larger multicenter retrospective analysis Baykaner et al have described that transseptal puncture can be safely and effectively performed with ICE, without the need for fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the use of ICE relates to better procedural endpoints and patient outcomes in PFA compared to the conventional fluoroscopy and a more ‘’tactile’’ approach remains to be investigated. In thermal ablation modalities, however, procedural outcomes of zero‐fluoroscopy approach have been shown to be comparable to the conventional fluoroscopy‐based approach 12 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that there are no significant differences in the success rate of different tachycardias ablation with any of both approaches. 2,13,[17][18][19][20] None of the patients in this series had structural heart damage, a fact that helps in the overall positive success rate, as showed in the study by Kawakami et al 21 They made extensive use of intracardiac echocardiography (ICE) and ultrasound-guided venous and atrial septal puncture (transesophageal echo), thereby obtaining a reduction in intervention-related complications. In the present cases, no further ultrasound support was required.…”
Section: Discussionmentioning
confidence: 99%
“…Prolic et al 18 showed a longer duration of the ablation procedures when performed without fluoroscopy, but Chen et al, 16 found that the difference between fluoroscopy-guided and 0-F procedures disappeared as the team acquired more experience with the navigation systems. This fact is usually attributed to the learning curve of the operators.…”
Section: Discussionmentioning
confidence: 99%